Pendidikan Karakter di Era Modern: Peran Manajemen Pendidikan dalam Membentuk Integritas dan Etika Peserta Didik (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the role of educational management in shaping students’ character through the strengthening of integrity and ethics within educational environments. The research employs a literature review method with a qualitative approach and descriptive analysis. Data were collected from scholarly articles indexed in Google Scholar and other credible academic sources published between 1977 and 2026. This is based on the importance of including classical literature and fundamental theories that serve as the conceptual foundation of character education and educational management, so that the study not only focuses on contemporary findings but also possesses a strong theoretical basis. From an initial pool of 50 articles, a rigorous selection process based on relevance and quality resulted in 32 articles being used as the primary sources of analysis. The findings indicate that character education cannot be separated from an effective educational management system, which includes structured planning, implementation, and evaluation. Furthermore, consistent implementation of character education has been shown to improve students’ discipline, responsibility, and ethical behavior. The limitations of this study lie in the use of a literature review and descriptive analysis, meaning that the findings depend on the available literature and the researcher’s interpretation. Further research is recommended to employ mixed methods and field studies in order to obtain more in-depth empirical data on the implementation of character education.